Usability evaluation of the operational interface of the NARERO learning system - YEN YU KANG; HSIN PEI LEE; T. J. E. JUAN; TAKAMITSU TANAKA; MITSUHIRO SETOYAMA; YUKARI CHIBA; SULEEPORN KAMCHOMPOO (Journal of Advanced Research in Social Sciences and Humanities, 2017)
Aim: This research aimed to examine the functionality and usability of NARERO’s administrative interface. As a means of analyzing user obstacles and providing recommendations, we looked at the blind spots in the NARERO learning system’s usage.Methodology: This research summarizes and organizes the issues with the NARERO learning system by collecting and analyzing data about people, events, and objects through observation, literature collection, and user evaluation. In addition, an objective experimental test was used to evaluate user satisfaction, and a Likert scale was employed to measure and analyze user evaluations and learning performance. Five professionals and forty high school students each gave their opinion on the system’s user interface in an objective experiment. In conclusion, system operations were carried out to aid in assessing academic performance.Findings: When looking at the expert evaluation results, most of the testers were pleased with how the NARERO learning system’s functions were designed. Furthermore, the system’s aesthetic design and usability could have been enhanced.Novelty/Implications: By learning and training the entire system, students can use the digital instruction system to select the course that best suits their interests and abilities.